Assinatura geoquímica de unidades coluviais da Bacia do Córrego do Rio Grande - Depressão de Gouveia/MG - Luiz Otavio Martins Cruz (2006)
Denudation events have been responsible, in Gouveia/MG Depression, for the deposition of colluvial units which cover slopes of the area. Previous works proposed that the soils of the area would have developed on colluvial materials. Latest research showed that some soils developed on autochthonous materials, reviewing previous hypotheses. This work aims to characterize those colluvial materials using physical and chemical analysis to contribute with interpretations concerning genesis and evolution of these materials. Soil samples were collected in five soil profiles from a catena and in other two profiles. These samples were collected from all soil horizons and stone lines presents and submitted to particle-size and quantitative analysis of the elements Si, Ti, Al, FeTotal, Mn, Mg, Ca, Na, K, P and Zr using X-ray fluorescence spectrometry. The results provided morphological, textural and chemical evidences that confirm the allochthonous origin of the pedological materials overlying stone lines. The main evide nces were: (i) identification of lithic fragments in incipient alteration degree in a highly weathered solum and the presence of these fragments in larger quantity in the stone lines than in the saprolite below; (ii) discontinuities among the C-horizon and solum materials point out by silt/clay and Zr/Ti ratios; (iii) distribution of the immobile elements Fe, Ti, Zr and Al with different patterns in relation to in situ development patterns, reflecting, partly, accumulation of loamier material in the base of the solum and sandier in the top, interpreted as textural difference provided by transport and deposition processes. The Zr/Ti ratio was considered best discontinuities marker, mainly in soils with different material sources and/or mineralogical composition. The relationship among soil distribution Cambisols in upper slope, Ferralsol in middle slope, Cambisol and Regosol in lower slope, respectively and stone lines distribution in the catena showed that the erosion processes are responsible by soils distribution and by the removal of materials of ancient colluvial deposits that still present in the concave portion of the slope. This relationship suggests that the soils have been developed over materials deposited on paleosurfaces composed of concave and convex elements. These soils have probably been submitted to simultaneous and continuous pedogeomorphological processes responsible for new pedogenesis and removal of part of the pedological cover, resulting in the re-configuration of the soils and slope. Although these processes suggest larger participation of the erosion in the relief forms of the research area, the current forms would possibly be product as much of geochemical processes as of erosion processes.xiv